Heavy load chain squats: a promising method for enhancing lower extremity explosive strength via post-activation performance enhancement - Wu, Dianxue; Feng, Shuo; Zhou, Aiguo; Xie, Yongmin (Frontiers in Physiology, 2025)
IntroductionPost-Activation Performance Enhancement (PAPE) is widely used to enhance explosive performance. Chain Squats (CS), as a form of variable resistance training, may offer advantages over Traditional Squats (TS) due to its load variability and neuromuscular stimulation characteristics. However, direct comparisons between the two under controlled conditions remain limited. Therefore, this study aims to compare the effects of CS and TS on PAPE to explore their different impacts on explosive strength.MethodsEighteen male participants completed CS and TS training at 90% of their 1RM in a randomized crossover design. Countermovement Jump (CMJ) tests were conducted at baseline and at 4, 8, 12, and 16 min post-intervention to evaluate Jump Height (JH), Peak Power (PP), Peak Rate of Force Development (PRFD), and Peak Impulse (PI).ResultsBoth CS and TS significantly enhanced explosive performance, but CS outperformed TS in several metrics. CS showed greater improvements in JH at 4 min (P < 0.01, η2 = 0.119, d = 3.69) and 8 min (P < 0.01, η2 = 0.102, d = 3.49). For PP, CS also outperformed TS with larger effect sizes at the same time points. PRFD showed no significant change in either modality, but CS showed a downward trend at 12 min (P = 0.055, η2 = −0.014, d = −424.16). PI peaked at 4 min in the CS group (P < 0.01, η2 = 0.019, d = 6.56), significantly outperforming TS.DiscussionCS significantly outperformed TS in enhancing JH, PP, and PI during the 4-8 min post-intervention period. Compared to TS, CS is a more advantageous PAPE strategy, offering a more effective way to enhance explosive performance in athletes.